2006
DOI: 10.1002/cphc.200500565
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Investigations into the Blue‐Shifting Hydrogen Bond in Benzene Complexes

Abstract: The benzene...X complexes (X=benzene, antracene, ovalene) were optimised at the MP2/6-31G** level with the C2v symmetry of the complex and planarity of the proton acceptor being preserved. The resulting stabilisation energies amount to 1.2, 2.3 and 2.9 kcal mol(-1), and the C-H bond of the proton donor is contracted by 0.0035, 0.0052 and 0.0055 A, respectively. The contraction is connected with a blue-shift of the C-H stretch vibration frequency. A two-dimensional anharmonic vibration treatment based on a MP2/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(9 citation statements)
references
References 20 publications
1
8
0
Order By: Relevance
“…For the T-shaped benzene dimer, the stem molecule can be considered as the hydrogen bond donor and the π electron cloud of the top molecule can be considered as the hydrogen bond acceptor. Earlier, a blue shifting hydrogen bond was proposed for the T-shaped benzene dimer by Hobza and co-workers. , Following the work by Erlekam et al, Hobza’s group has shown that the T-shaped structure that shows blue-shift is really a saddle point. The real minimum, which is slightly tilted, does show red-shift .…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…For the T-shaped benzene dimer, the stem molecule can be considered as the hydrogen bond donor and the π electron cloud of the top molecule can be considered as the hydrogen bond acceptor. Earlier, a blue shifting hydrogen bond was proposed for the T-shaped benzene dimer by Hobza and co-workers. , Following the work by Erlekam et al, Hobza’s group has shown that the T-shaped structure that shows blue-shift is really a saddle point. The real minimum, which is slightly tilted, does show red-shift .…”
Section: Resultsmentioning
confidence: 98%
“…The results from theoretical calculations vary and are highly dependent on the level of theory used. However, almost all the theoretical calculations agree that two possible isomers for the benzene dimer could exist: a T-shaped (TS) and a parallel displaced (PD). Calculating the global minimum structure of the benzene dimer is more complicated as it is floppy in nature.…”
Section: Introductionmentioning
confidence: 99%
“…13 A benchmark system in this connection, which has repeatedly been investigated both experimentally [14][15][16][17][18][19][20][21][22] and computationally is the benzene dimer. Ab initio investigations in the form of Møller-Plesset perturbation theory and coupled-cluster theory have paved the way for an understanding and accurate description of the most stable benzene dimer forms and the binding energies involved where especially the work of Sherill and co-workers, 26,28,29,31,35 that of Tsuzuki et al, [23][24][25]30 and the more recent works by Hill et al, 34 DiStasio et al, 38 Hobza and co-workers, 36,37,39 Janowski and Pulay, 40 and Lee et al 44 have to be mentioned. Symmetry-adapted perturbation theory ͑SAPT͒ has helped understand which of the benzene dimer forms is stabilized more by dispersion ͑-stacking͒, induction, or electrostatic forces.…”
Section: Introductionmentioning
confidence: 98%
“…12 In many cases, hydrogen is bonded to a carbon atom as the donor fragment, other examples are also known in which it is linked to an atom of a different element, such as Si, P and N. 13,14 Contrary to the case of red-shifting hydrogen bonding in which its origin is well-established and explained by electron charge transfer from lone pairs of the proton acceptor, Y, to the X-H s* antibonding orbital, [15][16][17][18] the origin of the blueshifting hydrogen bonding is still not well understood despite that it has received much attention from the literature where several explanations have been offered. [19][20][21][22][23][24] Hobza et al [25][26][27] have performed ab initio calculations for numerous blue-shifting complexes between hydrogen bond donors like haloform, X 3 C-H (where X is a halogen), with different hydrogen bond acceptors containing a p-electron system like benzene and fluorobenzene. In these studies, the authors have directed their investigations pointing out methodological issues as well as analyses of the electronic structure have been carried out, which were based on the Atoms in Molecules 28 and Natural Bond Orbital 29 analysis.…”
Section: Introductionmentioning
confidence: 99%
“…34 The blue-shifting experimental values observed in chloroform complexes agreed in good order with the theoretical prediction obtained by standard ab initio method treatment, MP2/6-31G(d), which has been widely used in the last decade. [25][26][27]35 Whereas in the interpretative issues, Hobza et al 25 proposed that the blue-shifting origin comes from electronic charge transfer from the proton acceptor, Y, to atoms bonded to X atom rather than to the X-H s* antibonding orbital, followed by electronic and structural rearrangements leading to a strengthening of the X-H bond. On the other hand, Hermansson 36 has drawn attention to the key role of the derivatives of the permanent dipole moment of X-H bond, this author concluded that a negative permanent dipole moment derivative along the vibrational coordinate, À dm 0 dr XÀH , is a necessary condition but it is not sufficient for a blue-shifting.…”
Section: Introductionmentioning
confidence: 99%